Is 24-hour Intraocular Pressure Monitoring Necessary in Glaucoma? - Mansouri, Kaweh (2013)
Although intraocular pressure (IOP) is the only treatable risk factor for glaucoma, its 24-hour behavior is poorly understood. Conflicting information is available in the literature with regard to the importance and predictive value of IOP peaks and fluctuations on the risk of glaucoma development and progression. This may be secondary to lack of prospective studies designed to address this issue. This article critically reviews the current evidence for the importance of 24-h IOP measurements in glaucoma and discusses shortcomings of current methods to assess 24-h IOP data, drawing attention to new developments in this field.